Perspektif Produsen Terhadap Keberkahan dalam Pengolahan Bahan Baku Onggok UD Mulyo - Dila Wahyuni; Nurul Wulandari (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
Blessings in the business world are a concept that describes sustenance that is not only abundant in material aspects, but also provides positive impacts, peace, and goodness for business actors and the wider community. This study aims to investigate the blessings experienced by producers in milling cassava flour at UD Mulyo, a business that focuses on processing cassava flour raw materials and realizing producer blessings through employee and community welfare and environmental empowerment. By applying a descriptive qualitative approach, data were obtained through in-depth interviews and observations, which were then analyzed thematically. The research findings show that blessings in UD Mulyo's business are realized through the application of Islamic values, such as honesty in business management, maintaining product quality, and a commitment to improving the welfare of employees and the surrounding community. UD Mulyo not only contributes to the economy through job creation and increasing community income, but also creates social benefits through harmonious cooperation with the local community. This study confirms that blessings in business go beyond material benefits, but also include spiritual values, social balance, and business sustainability.